Network medicine‐based multimodal omics analytic framework identifies immunometabolism endophenotypes underlying sex difference of Alzheimer's disease. (20th December 2022) - Cheng, Feixiong; Hou, Yuan; Zhou, Yadi; Xu, Jielin; Bekris, Lynn M.; Lathia, Justin D.; Pieper, Andrew A.; Leverenz, James B.; Cummings, Jeffrey
Abstract: Background: Although Alzheimer's disease (AD) is sexually dimorphic in prevalence, incidence, symptomology, and neuropathology, the molecular mechanisms underlying these sex differences are not well understood. Method: We presented a multimodal omics analytic framework to inspect sex differences in susceptibility to inflammation, cellular metabolism, and disease pathophysiology of AD. Specifically, we investigated the interplay between cellular metabolism and immune responses, termed the "immunometabolism endophenotype, " by unique integration of transcriptomics (single‐cell/nuclei RNA‐seq), proteomics (inflammatory biomarker expression), and metabolomics from the AD knowledge portal, the Alzheimer's Disease Metabolomics Consortium, and the Cleveland Alzheimer's Disease Research Center (CADRC). Result: We identified sex‐specific, elevated pro‐inflammatory gene/protein expression in blood (including myeloid‐derived suppressor cells [MDSCs]) and cerebrospinal fluid of phenotypically characterized subjects by AD biomarkers of A myloid deposition, pathologic T au, and N eurodegeneration (ATN). We also identified sex‐specific microglial gene signatures in AD patient brains from single‐cell/nuclei RNA‐seq (sc/snRNA‐seq) data analyses. We further found that women lost gene expression of innate and adaptive pathways (i.e., NF‐kappa B signaling, Toll‐like receptor signaling, and HIF signaling) in microglia compared to men with amyloid and tau neuropathology. However, women have elevated expression of innate and adaptive pathways (i.e., IL‐17 signaling and antigen processing and presentation) in excitatory neurons compared to men with tau neuropathology. Integrative sc/snRNA‐seq data analyses showed sex‐specific ligand‐receptor interactions among microglia, astrocytes, and neurons. We also found that women with AD have elevated metabolites of glycerophospholipids and sphingolipids compared to men with AD. A microglia‐specific male‐biased metabolite‐enzyme network is enriched in immune pathways of Type I and II IFN signaling and fructose, mannose, and HIF‐1 metabolic pathways. By contrast, the female‐biased metabolite‐enzyme network is significantly enriched in glycerophospholipids. These findings were further validated by the female‐biased expression of pro‐inflammatory cytokines (i.e., IFNγ, GM‐CSF, IL‐8, and IL‐15) from ATN‐characterized cohorts from our CADRC. Conclusion: This study establishes proof‐of‐concept of sex‐specific immune responses, cellular metabolism, and microglial immunometabolism underlying sex differences in AD.